2014
DOI: 10.4314/ijbcs.v8i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary energy level on growth performance and morphometric parameters of local barred chickens at the starter phase

Abstract: An experiment was conducted to determine the influence of dietary energy level on the growth performance and morphometric characteristics of local barred chicks. The experiment lasted for 12 weeks. Three hundred and twenty day-old barred chicks were assigned to four different dietary treatments, having four replicates of 20 chicks each. Treatments consisted of D0, D1, D2 and D3 containing 2700, 2800, 2900 and 3000 kcal/kg of metabolisable energy respectively. The highest BW (868 g) and BWG (830 g) were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The external body measurements recorded during present study is in line with the findings of Kuietche et al (2014) who recorded mean beak length 3.26±0.18cm, body length 32.12±1.92cm and body girth 24.08±1.64cm in turkeys. Jankowski et al (2012) recorded thigh length 11.7cm at the age of 18 weeks in turkeys.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The external body measurements recorded during present study is in line with the findings of Kuietche et al (2014) who recorded mean beak length 3.26±0.18cm, body length 32.12±1.92cm and body girth 24.08±1.64cm in turkeys. Jankowski et al (2012) recorded thigh length 11.7cm at the age of 18 weeks in turkeys.…”
Section: Discussionsupporting
confidence: 91%
“…Green (2001) reported 3.53cm tarsus length and Buchholz (1995) reported snood length ranging from 4cm to 6cm in turkeys. Kuietche et al (2014) reported wing length of 20.45±1.75cm in turkeys at 12 th week of age. Heavier males have longer spurs as compared to the lighter ones and spent more time in display and movements around females.…”
Section: Discussionmentioning
confidence: 95%
“…It's therefore evidenced that lower egg weight at incubation will affect the keet weight at hatch and reduce subsequent growth performances of the young birds (Figures 1, 2, 3 and 4). Nguefack et al, (2022) reported much lower live weight (< 500 g in all treatments) at 8 weeks of age with varied levels of crude protein in diet of guinea fowl compared to what was obtained in this present study. Keets from small egg weight category had even better live weight (512.5 g) at 8 weeks of age, followed by those from the medium category (522.9 g) and the large category (605.42 g) compared to the average live weight reported by Nguefack and co.…”
Section: Relationship Between Egg Weight G/ Egg) On Hatchability and ...contrasting
confidence: 65%
“…We could explain the performance drop with the dose of 4.5%, by the exceeding of optimal level of energy needed to chickens. Kuietche et al (2014) made a similar observation about local barred chicks that have recorded higher feed conversion ratio when energy level in the ration is less than 2700 kcal / kg or greater than 2900kcal / kg. It could also be due to a decrease of digestibility of the feed due to sorghum used for the probiotic feed ingredient production.…”
Section: Feed Conversion Ratio (Fcr)mentioning
confidence: 58%